Halal healthcare services: patients’ satisfaction and word of Mouth lesson from islamic-friendly hospitals - Muhammad Khalilur Rahman; Noor Raihani Zainol; Noorshella Che Nawi; Ataul Karim Patwary; Wan Farha Wan Zulkifli; Md Mahmudul Haque (Molecular Diversity Preservation International (MDPI), 2023)
This study aims to investigate the impact of halal healthcare attributes, intrinsic value, and extrinsic value on satisfaction, and explores how patient satisfaction with halal healthcare services influences word of mouth (WOM) to others. The cross-sectional survey was conducted in two cities with four Islamic-friendly hospitals across Malaysia. This study used purposive and non-probability random sampling methods. Partial least square (PLS) technique was used for data analysis of 309 Muslim patients with a response rate of 61.8%. Findings revealed that hospital’s halal healthcare attributes (β = 0.225, p < 0.01), hospital’s intrinsic value (β = 0.432, p < 0.01), and hospital’s extrinsic value (β = 0.196, p < 0.01) have significant influence on patient satisfaction with halal healthcare service, which in turn reflects the WOM to others (β = 0.692, p < 0.01). The results identified that satisfaction mediates the effect of hospital’s halal attributes, as well as hospital’s intrinsic and extrinsic values on WOM. These findings will contribute to healthcare service providers and academicians for further study to improve a framework for establishing a standard for halal healthcare service for patient satisfaction and WOM to others in Islamic-friendly hospitals.